Tools to balance increased food security with decreased emissions - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Almost every aspect of trying to reduce climate change involves weighing alternatives and then setting priorities. For example, you could plant trees to store carbon, but that might reduce the amount of food you can grow on the same land. Or you could add fertilizers to boost food production, but that might need more energy and could increase emissions of greenhouse gases (GHGs). Decision makers planning for climate change need to steer an optimal course that balances reducing emissions with sustaining future food production and protecting environmental health. Yet the information needed to plot that course is usually unavailable, especially in low-income countries, because models require huge amounts of data and hours of computer time. The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) is working to make information about the impacts of various mitigation measures available, so that policy makers can reach better-informed decisions.